2023
DOI: 10.1007/s11270-023-06279-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Air Pollution Characteristics and Multi-scale Meteorological Factor Variability Analysis of Mega-mountain Cities in the Chengdu-Chongqing Economic Circle

Abstract: Currently, air quality has become central to global environmental policymaking. As a typical mountain megacity in the Cheng-Yu region, the air pollution in Chongqing is unique and sensitive. This study aims to comprehensively investigate the long-term annual, seasonal, and monthly variation characteristics of six major pollutants and seven meteorological parameters. The emission distribution of major pollutants is also discussed. The relationship between pollutants and the multi-scale meteorological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…S5) [74]. Furthermore, the unique climatic features of this region are extremely low wind speeds (0.9-1.4 m/s), a high frequency of atmospheric inversions and high relative humidity (79-84%) all year round [10,[75][76][77]. The closed environment makes the stability of the atmospheric stratification in the basin boundary layer higher than that in other areas at the same latitude.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…S5) [74]. Furthermore, the unique climatic features of this region are extremely low wind speeds (0.9-1.4 m/s), a high frequency of atmospheric inversions and high relative humidity (79-84%) all year round [10,[75][76][77]. The closed environment makes the stability of the atmospheric stratification in the basin boundary layer higher than that in other areas at the same latitude.…”
Section: Study Areamentioning
confidence: 99%
“…Recent population research have revealed that PM 2.5 exposure is related to reproductive and neurological diseases, while O 3 exposure is associated with cardiopulmonary disease and lung cancer [8,9]. Previous studies have shown that about 7 million premature deaths per year are due to air pollution [10,11]. Previous studies also indicate that about 98% of cities in developing countries fail to fulfill the air quality guidelines of World Health Organization (WHO) [12,13].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation